African tick bite fever in returning Swedish travellers. Report of two cases and aspects of diagnostics. Issue 1 (1st January 2017) - Nilsson, Kenneth; Wallménius, Katarina; Rundlöf-Nygren, Pernilla; Strömdahl, Susanne; Påhlson, Carl
ABSTRACT: Introduction : African tick-bite fever, caused by Rickettsia africae, is endemic in rural areas of sub-Saharan Africa and a possible cause of fever in returning Swedish travellers. Two patients are presented, and the advantages and disadvantages of different diagnostic methods are discussed. Patients and methods : Two middle-aged men fell ill with fever after returning home from South Africa. Both had single eschars and one also presented with a lymph node swelling. Samples were taken for serology, general bacterial culture from the wound (Patient 1) using a swab and additionally for Patient 2 PCR of a skin biopsy from the eschar. Results and discussion : Both patients seroconverted one month after onset. Real-time PCR of the biopsy was positive, where sequencing of the gltA gene was 99–100% consistent with R. africae . A drop of fluid from the biopsy contained a sufficient number of bacteria to also allow for isolation of rickettsiae in Vero cell culture. Direct molecular detection by PCR from a swab used for bacteria culture from the eschar from Patient 1 also yielded a positive result. In conclusion, the findings highlight the usefulness of swabs for early non-invasive diagnosis of African tick-bite fever in febrile travellers.